Cage Retropulsion after Transforaminal Lumbar Interbody Fusion Surgery: Case Report - Paudel, Bishal; Bijukachhe, Binod; Dahal, Ram Krishna; Shrestha, Aayush (Grande Medical Journal, 2025)
Cage Retropulsion is an uncommon complication following transforaminal lumbar interbody fusion (TLIF) surgery. The estimated rate of cage retropulsion has reportedly been < 1% in previous studies. Risk factors for cage retropulsion after lumbar interbody fusion surgery includes patient related factors, radiological findings, surgical procedure-related factors and postoperative factors. In the event of retropulsion, revision surgery should be performed for patients with neurologic deficits or clinically symptomatic, and conservative treatment is encouraged in patients who are asymptomatic.